Urgensi Pengesahan RUU Penghapusan Kekerasan Seksual Sebagai Realitas Tingginya Angka Kekerasan Seksual Di Indonesia: Urgensi Pengesahan RUU Penghapusan Kekerasan Seksual Sebagai Realitas Tingginya Angka Kekerasan Seksual Di Indonesia - Setiawan Adiputra; Agsel Awanisa; Yemima Hotmaria Purba (Faculty of Law, Universitas Lampung, 2022)
The challenging aspect of a large number of sexual violence in Indonesia currently makes the draft law on the Elimination of Sexual Violence included in the National Legislation Program Priority 2021. For this reason, the government is expected to ratify the draft law on the Elimination of Sexual Violence to regulate sexual violence comprehensively. The goal of this study is to determine the evolution of data on sexual violence in Indonesia and to assess the urgency of ratifying the draft law on sexual violence elimination in light of the reality of the high number of sexual violence in Indonesia. This study employs a normative legal research method with statutory, conceptual, and case approaches. According to the findings of this study, sexual violence crimes continue to rise in a variety of forms, including not only physical contact but also non-physical contact. Several factors contribute to the high rate of sexual violence, including the structural readiness of institutions and human resources to deal with sexual violence crimes remains very low. Substantially, existing regulations have not comprehensively accommodated various forms of sexual violence, so there is no legality to serve as a foundation for preventing, dealing with, and recovering victims of sexual violence. Thus, the Act on the Crime of Sexual Violence (UU TPKS) is currently an urgent matter as a social control to reduce and overcome the occurrence of sexual violence.